The technical parameters of the creation process for kayak paddles as a sport product - Simkus, A.; Navickas, V.; Vveinhardt, J.; Alekrinskis, A. (Annals of Applied Sport Science, 2020)
Background. Considering that a personchr('39')s physical and psychological possibilities are not limitless, the technical means used by athletes are of great importance. In order to achieve high results in the kayak sprint competition, users-athletes orient to the highest quality products; therefore, a significant task falls to their manufacturers to analyze the competitorschr('39') products, evaluate userschr('39') needs at the maximum, and look for new technical solutions. Quality function deployment (QFD) is one of the methods, the use of which in the creation of high-quality paddles for the kayak sports competition is a relevant object of scientific research. Objectives. The purpose of this empirical study is to establish kayak paddle technical parameters for a sprint event deploying the extended quality function method. The article analyses the concept of quality function deployment, specifying opportunities for quality function deployment method applications when producing a new product. Methods. The research comprises three major phases: the first one is a verbal survey, applying the method of half structural interview, the second one is written survey on the respondents`, prize holders`, from nine European countries (Lithuania, Hungary, German, Russia, Byelorussia, England, Australia, Spain, and Romania) responses and the third one - quality house matrix producing backing on the results of calculations and experts opinions. Results. Based on the impact of technical requirements and impact comparative weight indexes, priorities of technical parameters for consumers` - rowers kayak paddle sprint events were established, which should be implemented first and foremost. Criteria such as the structure of the product material, rigidness, structure of carbon fiber, and the number of fabric layers were indicated. Conclusion. Based on the results of the study, it has been found that in order to create a kayak paddle for the sprint competition, which meets the userschr('39') needs, the greatest focus should be placed on the implementation of such needs as paddle blade parameters, paddle shaft parameters, durability, and grip between the arm and paddle, as the participants of the study confirmed that they are of paramount importance for users. This study extends the limits of applicability of the QFD method in developing new and improving the already existing products, including a specific field - the paddle for the kayak sprint competition, and also partially addresses the problem of the lack of research on using the scientific research method in the development of sports products. Therefore, in the future, it is recommended to develop research on the application of the QFD method in the creation of various sports products.